Challenging surgery of giant right coronary aneurysm associated with coronary sinus fistula. Issue 10 (3rd July 2019) - Micovic, Slobodan V.; Zivkovic, Igor S.; Milacic, Petar A.; Vukovic, Petar M.; Kecmanovic, Vladimir Z.; Jovovic, Ljiljana I.; Bulatovic, Nebojsa
Abstract: Coronary artery fistula is a rare congenital or acquired anomaly. It involves an abnormal connection between the coronary artery and the cardiac chambers or the large thoracic vessels. In some cases, the feeding coronary artery can become extremely dilated. The treatment includes a transcatheter or a surgical intervention depending on the complexity of the anomaly. We present the surgical treatment of the coronary artery to coronary sinus fistula, which includes the complete exclusion of the giant right coronary artery and followed by triple bypass surgery.